2017
DOI: 10.12659/ajcr.905684
|View full text |Cite
|
Sign up to set email alerts
|

Extremely High Serum Ferritin: An Instrumental Marker of Masquerading Adult-Onset Still’s Disease with Hemophagocytic Syndrome

Abstract: Patient: Female, 88Final Diagnosis: Adult onset still’s diseaseSymptoms: Fever • rashMedication: —Clinical Procedure: —Specialty: RhaumatologyObjective:Unusual clinical courseBackground:Adult-onset Still’s disease (AOSD) is a rare multi-systemic inflammatory disorder of unknown etiology characterized by spiking fever, characteristic rash, and arthritis. It often associates with high serum ferritin levels.Case Report:An 88-year-old woman had fever of over 39°C without response to extended-spectrum antibiotics f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Regarding the clinical outcome, the rates of remission, relapse and death were similar, but the observation period was longer in the overall AOSD group. Next, we identified 5 EOSD cases complicated by MAS, including the present case (8,15,28,29), and compared the findings with AOSD cases complicated by MAS from the literature review (46) ( Table 4). The mean onset age of MAS was 76.8±7.3 and 40.2±16.0 years old in the EOSD and AOSD groups, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the clinical outcome, the rates of remission, relapse and death were similar, but the observation period was longer in the overall AOSD group. Next, we identified 5 EOSD cases complicated by MAS, including the present case (8,15,28,29), and compared the findings with AOSD cases complicated by MAS from the literature review (46) ( Table 4). The mean onset age of MAS was 76.8±7.3 and 40.2±16.0 years old in the EOSD and AOSD groups, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, some cases of elderlyonset Still's disease (EOSD) have also been reported . The oldest such case was 88 years old at the disease onset (8). The frequency of EOSD is so low that the literature is limited to only a few case reports, with no reviews available, so the overall clinical features of EOSD remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The general medicine department of this hospital manages the first-touch practice of outpatients without a reference from their primary doctors, in addition to treating both in-and outpatients with common diseases, fevers of unknown origin, diseases that are difficult to correctly diagnose, and complicated pathological situations requiring intensive care. [4][5][6][7] In this study, patients suspected of having, or diagnosed with IE before admission would, in principle, be seen by the endocarditis team of the department of cardiology and cardiovascular surgery. In comparison, patients with non-specific symptoms and signs such as fever of unknown origin, consciousness disorder, paralysis, or rash, who were not suspected of having, or were not diagnosed with IE prior to referral, would initially be seen by the department of general medicine, emergency medicine, neurology, or dermatology or whatever department seemed appropriate.…”
Section: Settingmentioning
confidence: 99%
“…3 Among these departments, the general medicine departments, especially at university hospitals in Japan, which are often in charge of diagnosing diagnostically challenging diseases, including fevers of unknown origin, are likely to see patients with IE. [4][5][6][7] Our previous research showed that the general medicine department of Saga University Hospital in Japan diagnosed and treated the third-highest number of inpatients with IE after the departments of cardiology and cardiovascular surgery. 4 The department of cardiovascular surgery plays a clearly delineated role in treating IE in terms of when and how to operate and how to manage patients after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The first disorder, disseminated intravascular coagulation (DIC), is not rare and may occur at a frequency of 1-5% [8,53,[59][60][61][62][63][64][65][66][67]. This diagnosis should be suspected with the combination of thrombotic events and cutaneous or mucosal bleeding and sometimes specific organ involvements, such as fulminant hepatitis, cardiac or respiratory failure, or stroke.…”
Section: Coagulation Disordersmentioning
confidence: 99%